Integrating Intersectionality Into the Exposome Paradigm: A Novel Approach to Racial Inequities in Uterine Fibroids - Zota, Ami R. (Am J Public Health, 2021)
Intersectionality is a critical theoretical framework that emphasizes the influence of intersecting systems of oppression on the lived experiences of people marginalized by inequity. Although applications of intersectionality are increasing in public health, this framework is absent in environmental health, which has instead focused on the exposome, a paradigm that considers the totality of an individual’s environmental exposures across the life course. Despite advancements in the biological complexity of exposome models, they continue to fall short in addressing health inequities. Therefore, we highlight the need for integrating intersectionality into the exposome. We introduce key concepts and tools for environmental health scientists interested in operationalizing intersectionality in exposome studies and discuss examples of this innovative approach from our work on racial inequities in uterine fibroids. Our case studies illustrate how interlocking systems of racism and sexism may affect Black women’s exposure to environmental chemicals, their epigenetic regulation of uterine fibroids, and their clinical care. Because health relies on biological and social–structural determinants and varies across different intersectional positions, our proposed framework may be a promising approach for understanding environmental health inequities and furthering social justice.